2020
DOI: 10.3390/ma13040906
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Small Clear Specimens of Eucalyptus globulus Labill

Abstract: Eucalyptus globulus Labill stands out as one of the hardwood species produced in Europe with prominent mechanical properties, which is undergoing a growing interest in extending added value. The development of engineered wood products with this species and its application in timber structures involving numerical finite element simulations requires knowledge of the mechanical properties for the different orthotropic material directions. The aim of the present study is to determine the main mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Consistent with previous findings on other species [11], along the grain, a higher tensile failure strength was found than that under compression both above and below the FSP, i.e., the compressive strength of the wood was almost two times lower than the tensile strength. This agreed with previous studies on dry wood, which showed that wood is an anisotropic material with different strengths in tension and compression [29,32]. This anisotropy is due to the cellular nature of wood and its growth.…”
Section: Failure Envelopes and Failure Strengthssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings on other species [11], along the grain, a higher tensile failure strength was found than that under compression both above and below the FSP, i.e., the compressive strength of the wood was almost two times lower than the tensile strength. This agreed with previous studies on dry wood, which showed that wood is an anisotropic material with different strengths in tension and compression [29,32]. This anisotropy is due to the cellular nature of wood and its growth.…”
Section: Failure Envelopes and Failure Strengthssupporting
confidence: 92%
“…The fibre-directed tensile failure mode was classified according to its shape [29]. The failure mode linked strongly with its grain angle, as shown in Figure 8.…”
Section: Failure Modesmentioning
confidence: 99%
“…Analyzing the shear strength behavior, the value obtained in the experimental program, 12.14 MPa, is consistent with the literature: 16. [1]. It is important to note that the value obtained for the shear strength is significantly higher than the characteristic value reported for the strength class D40 by EN 338 [27] (3.8 MPa).…”
Section: Discussionmentioning
confidence: 58%
“…The increasing political and social demands regarding the use of eco-friendly building materials are leading in recent years to a strong rise in the use of wood due to its CO 2 absorption capacity and the quality of renewable natural resource [1]. In recent studies of the UK construction sector, it has been shown that novel off-site panelized modular timber frame systems can save up to 50% of embodied carbon and 35% embodied energy when compared with traditional residential building methods and materials [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, a remarkable share of the forest industry investments is now going to fast-growing markets in Asia and low-cost production regions, such as South America [14]. Among the different species available, Eucalyptus stands out in terms of availability, sustainability, price [22], and mechanical performance [23][24][25]. Hence, it may be an alternative to hardwood species for the wood flooring industry [26,27].…”
Section: Introductionmentioning
confidence: 99%